1993
DOI: 10.1016/0014-5793(93)81547-d
|View full text |Cite
|
Sign up to set email alerts
|

A brain‐specific transcript from the 3′‐terminal region of the skeletal muscle ryanodine receptor gene

Abstract: We have shown previously that the skeletal muscle ryanodine receptor mRNA of -16,000 nucleotides codes 5,037 amino acid residues constituting the calcium release channel in skeletal muscle. In this study, RNA blot hybridization analysis shows that the brain contains an RNA species with an estimated size of -2,400 nucleotides hybridizable with the 3'-terminal region of the skeletal muscle ryanodine receptor cDNA. cDNA cloning and genome analysis indicated that two transcripts differing in their start sites are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In contrast, three amplified cDNA fragments were observed when RNA from brain was used as the template under the same conditions. The results are consistent with the distribution of the RyR subtype mRNAs examined previously by Northern blot and in situ hybridization analysis (Hakamata et al, 1992;Takeshima et al, 1993;Furuichi et al, 1994). The [Ca2+]i rise induced by caffeine results in contractions of cultured muscle cells from both dyspedic and control mice.…”
Section: Introductionsupporting
confidence: 91%
“…In contrast, three amplified cDNA fragments were observed when RNA from brain was used as the template under the same conditions. The results are consistent with the distribution of the RyR subtype mRNAs examined previously by Northern blot and in situ hybridization analysis (Hakamata et al, 1992;Takeshima et al, 1993;Furuichi et al, 1994). The [Ca2+]i rise induced by caffeine results in contractions of cultured muscle cells from both dyspedic and control mice.…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies have reported that the ER retention signal is likely present within the COOH-terminal portion of RyR1 (9,53,78) or RyR2 (22), which contains transmembrane domains (TMDs). Bhat and Ma (9) reported that amino acids 4918 -4943 of RyR1, which are within TMD6 and have a consensus sequence with the IP 3 receptor and RyR2, contain a strong ER retention signal (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RyR expressed in heterologous cells is localized to the ER membrane, suggesting that the signal(s) responsible for intracellular localization of RyR is present within its primary amino acid sequence (3,9,10). Using fusion proteins of RyR and green fluorescent protein (GFP) expressed in CHO cells, we have observed that the C-terminal portion of RyR contains sequence(s) responsible for its ER localization (3).…”
Section: Cule (Icam) Various Fragments Of Ryr and Green Fluorescentmentioning
confidence: 99%